RELATIONAL PROCESS IN THE NEWSPAPER OF THE JAKARTA POST EDITION OF FEBRUARY 2015 – JUNE 2015: A FUNCTIONAL GRAMMAR APPROACH - Wanodyatama, Nike Puspita (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2019)
In this research, researcher concerns with one of the language metafunctions only that is the representation clause. This research is entitled ‘Relational Processes in The Jakarta Post Newspaper’. This research attempts to investigate the usage of relational processes. Therefore, the method is used descriptive and the study is focused on verbs in the relational processes in the Jakarta Post. The research shows the relational process described as a relation set up between two entities. The English system operates with three main types of relation: intensive, possessive or circumstantial, and each of these comes in two distinct modes of being – ‘attributive’ and ‘identifying’. In conclusion, in the exploration study are found the types of verbs of attribution and the circumstance expressed by the verb. Moreover, the type of verbs attribution, verbs of identification and the circumstance is expressed by the verbs which can be glossed as perception of the attribute, verbs in attributive process clauses has to do with change, and some circumstantial meaning which is incorporated with the type of verbs.